Gel Properties and Interaction Mechanism of Heat-Induced Lentinan–Chicken Myofibrillar Protein - Kexin Li; Ya Ren; Yong Li; Liang Li; Yanfen Cheng; Shaojun Yun; Feier Cheng; Wenfei Zhao; Li Zhao; Mingchang Chang; Jinling Cao; Cuiping Feng (Foods)
The enhancement of gel properties in chicken myofibrillar proteins (MPs) is a crucial objective in meat processing. In this experiment, we systematically investigated the effects of lentinan (LNT) on MP gel formation ability and three-dimensional network structure features through multi-scale structural characterization and molecular interactions analysis and elucidated the molecular pathways of their molecular actions in regulating gel properties. The addition of LNT (0–2%, w/v) significantly enhanced the water-holding capacity (WHC), textural, and rheological properties of LNT-MPs. As the concentration of LNT increased, the hydrophobic and electrostatic interactions became more pronounced. Conversely, the contribution from disulfide bonds exhibited an inverse relationship, with hydrogen bonds demonstrating the least impact. Subsequently, the α-helix content decreased from 23.75% to 22.64%, and the β-fold content increased from 28.03% to 29.22%, suggesting that the protein aggregates reorganized to form larger aggregates, which contributed to forming a more stable network structure of gels. This investigation establishes LNT’s capacity to modify the gelation mechanisms of MPs. These outcomes offer crucial insights for implementing fungal polysaccharides in processed meat product development.